Towards the integration of pharmacogenetics in psychiatry: a minimum, evidence-based genetic testing panel. Issue 1 (January 2019) - Bousman, Chad; Maruf, Abdullah Al; Müller, Daniel J.
Abstract : Purpose of review: The implementation of pharmacogenetic testing in psychiatry is underway but is not yet standard protocol. Barriers to pharmacogenetics becoming standard practice are the lack of translation of evidence-based recommendations and standardization of genetic testing panels. As for the latter, there are currently no regulatory standards related to the gene and allele content of testing panels used to derive medication selection and dosing advice. To address these barriers, we summarize the current gene–drug interaction knowledgebase and proposed a minimum gene and allele set for pharmacogenetic testing in psychiatry. Recent findings: The Pharmacogenomics Knowledgebase has cataloged 448 gene–drug interactions relevant to psychiatry based on the current scientific literature, drug labels, and pharmacogenetic-based implementation guidelines. A majority of these interactions involved two cytochrome P450 enzymes ( CYP2D6 and CYP2C19 ) and antidepressant medications, however, CYP2C9, HLA-A, and HLA-B are relevant to mood stabilizers/anticonvulsants. Summary: On the basis of evidence base, we proposed a minimum gene and allele set for pharmacogenetic testing in psychiatry that includes 16 variant alleles within five genes ( CYP2C9, CYP2C19, CYP2D6, HLA-A, HLA-B ). The intent is to assist clinicians in judging the gene and allele content of pharmacogenetic tests and to facilitate pharmacogenetic testing as a standard protocol and companion tool for psychotropic medication selection and dosing.